Effects of Isorhamnetin in Human Amniotic Epithelial Stem Cells in vitro and Its Cardioprotective Effects in vivo - Aonuma, Kazuhiro; Ferdousi, Farhana; Xu, DongZhu; Tominaga, Kenichi; Isoda, Hiroko (Frontiers in Cell and Developmental Biology, 2020)
Cardiac hypertrophy and fibrosis are major pathophysiologic disorders that lead to serious cardiovascular diseases (CVDs), such as heart failure and arrhythmia. It is well known that transforming growth factor-β (TGF-β) signaling pathways play a major role in the proliferation of cardiac hypertrophy and fibrosis, which is mainly stimulated by angiotensin II (AgII). This study aimed to investigate the eﬀect of isorhamnetin (ISO) in vivo and in vitro. In vitro, enhanced biological processes including TGFβ, collagen-related functions, and inflammatory processes were significantly suppressed by ISO pretreated human amniotic epithelial stem cells (hAESCs). In vivo, continuous AgII infusion using an osmotic pump induced significant pathological fibrosis and myocardial hypertrophy, which were remarkably suppressed by ISO pretreatment in mice. ISO was found to reverse the enhanced TGF-β and col1a1 mRNA expression induced by AgII exposure, which causes cardiovascular remodeling in ventricular cardiomyocytes. These findings indicated that ISO could be a potential agent against cardiac hypertrophy and fibrosis induced by AgII.